Discussions on the Vertex Euclidean Properties of Graphs (Contemporary Mathematics, 2024)
In 2022, the result that the sum of the lengths of any two edges of a triangle is greater than the length of the third edge in Euclidean geometry, is applied to labeling graph theory, a new concept-the vertex Euclidean graph is introduced. A simple graph G = (V, E) is said to be vertex Euclidean if there exists a bijection f from V to {1, 2, ..., |V|} such that f(u) + f(v) > f(w) for each C3 subgraph with vertex set {u, v, w}, where f(u) < f(v) < f(w). The vertex Euclidean deficiency of a graph G, denoted µvEuclid(G), is the smallest positive integer m such that G ∪Nm is vertex Euclidean. In this paper, the sufficient condition that the disjoint union of G and H is vertex Euclidean is given, meanwhile, the vertex Euclidean properties of four classes graphs are discussed, the vertex Euclidean deficiency of these graphs are obtained.
Keywords: vertex Euclidean graph; vertex Euclidean deficiency; Circ(n, 2); Zykov sums of a cycle and a m null graph; k-level X-grid; generality triangular snake